Uniaxial compressive behavior of circular concrete columns actively confined with Fe-SMA strips. (15th March 2022) - Zerbe, Lara; Vieira, Dario; Belarbi, Abdeldjelil; Senouci, Ahmed
Abstract: An increased interest in the strengthening and rehabilitation of deficient or deteriorated structures took place in the past few decades to maintain the sustainability and integrity of existing structures. Different strengthening techniques have been recently studied and used to retrofit or strengthen concrete elements. One of these techniques is the use of Shape Memory Alloys (SMA), taking advantage of its shape memory effect property. This property allows the application of an initial confining pressure, called active confinement, when the material is restrained. Such pressure is developed when the material undergoes phase transformations upon heating to a certain temperature. As a result of their unique properties, different types of SMA for different structural engineering applications have been studied. In this paper, an experimental program was conducted to evaluate the behavior of concrete columns confined with iron-based SMA (Fe-SMA) strips under uniaxial compressive loading. A total of 25 circular columns were tested, and the results were analyzed to identify the influences of selected parameters: 1) presence of internal reinforcement, 2) initial confining pressure, and 3) ratio of external SMA confinement. The test results indicated great improvement in the overall behavior of the confined columns, especially their axial deformation capabilities. In addition, an analytical approach was proposed to model the axial load-deformation behavior of the actively confined columns. The proposed expressions showed to adequately capture the axial behavior of the columns, and the obtained results were in good agreement with the experimental test results of columns confined with Fe-SMA strips.